Power revolution in the industrialization of Japan, 1885-1940 - Minami, Ryoshin (Kinokuniya Co., 1987)
Contents: The remarkable industrial growth in pre-World War II Japan was closely associated with changes in the mechanisms that powered the machines of industry: the expansion of the power supply, the mechanization of previously non-powered factories, and the transition from water wheels to steam engines to electric motors. Here, economic historian Ryoshin Minami details this power revolution, analyzing its beginnings and evolution up to 1940